World Statistics Pocketbook 2011 - United Nations Department of Economic; Social Affairs (United Nations, 2012)
The 31st edition of this annual publication compiles over 50 indicators collected from more than 20 international statistical sources and presented in one-page profiles for 216 countries or areas of the world. This issue covers various years from 2000 to 2011. For the economic indicators, in general, three years — 2000, 2005 and 2010 — are shown; for the indicators in the social and environmental categories, data for one year are presented. The topics covered include: agriculture, balance of payments, education, energy, environment, food, gender, health, industrial production, information and communication, international finance, international tourism, international trade, labour, migration, national accounts, population and prices.